2017
DOI: 10.7717/peerj.3369
|View full text |Cite
|
Sign up to set email alerts
|

Increasing game prices may alter farmers’ behaviours towards leopards (Panthera pardus) and other carnivores in South Africa

Abstract: Human-carnivore conflict occurs globally, particularly in regions where large carnivores predate livestock. Retaliatory killings do occur, and although predation of livestock by carnivores happens, losses from other factors such as disease or injury can be misattributed because of landowner perceptions. Game farming for both trophy hunting and eco-tourism is becoming increasingly common in South Africa, and there has been a rapid increase in the cost of game animals (in some species as much as five-fold) betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…An annual harvest rate of 0.4 leopards/100 km 2 was determined (Thorn et al, 2012), and this density equals the leopard density in some reserves in NWP, such as Madikwe (Mann et al, 2018). In the MP cluster, an off‐take of 3–5 leopards/100 km 2 has been reported (Pirie, 2016), which is not sustainable. Over‐harvest is known to disrupt the spatial organization in carnivores due a high population turn‐over and increased home‐range vacancies (Frank et al, 2018; Newby et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…An annual harvest rate of 0.4 leopards/100 km 2 was determined (Thorn et al, 2012), and this density equals the leopard density in some reserves in NWP, such as Madikwe (Mann et al, 2018). In the MP cluster, an off‐take of 3–5 leopards/100 km 2 has been reported (Pirie, 2016), which is not sustainable. Over‐harvest is known to disrupt the spatial organization in carnivores due a high population turn‐over and increased home‐range vacancies (Frank et al, 2018; Newby et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Almost all farmers in our study area suffered livestock losses attributed to predators, with jackal and caracal, followed by Cape fox and baboons considered the main predators. Jackal, caracal and different species of baboons have been reported to kill livestock in other studies as well [ 54 ], including outside of South Africa [ 55 ]. In the main small-livestock areas of South Africa, jackal and caracal predation have been shown to respectively account for 65% and 30% of predation losses overall [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence also suggested that introducing non‐native herbivore (Castley et al., 2001) and carnivore species (e.g. tigers; Snijders, 2018), game protective fencing (Woodroffe et al., 2014) and removing predators to protect trophy animals (Pirie et al., 2017), all in response to trophy hunting demand, have deteriorated local biodiversity. Moreover, fuelled by rising auction prices, captive breeding of trophy animals affected biodiversity by having evolutionary consequences such as inbreeding in animal populations (Castley et al., 2001) and artificially creating ‘new species’ through hybridization, splitting and crossbreeding (e.g.…”
Section: Utilitarianismmentioning
confidence: 99%